IMPLEMENTASI APLIKASI PEMBELAJARAN UNTUK ANAK BERBASIS ANDROID - Sam'ani Sam'ani; Sutami Sutami; Muhammad Haris Qamaruzzaman (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Permendiknas No. 16/2007 concerning Academic Qualification Standards and Teacher Competence, Pedagogical Competence of 5th / Senior High School teachers says that